Multidimensional analysis of the evolution of the COVID-19 pandemic in countries of the Americas (2022)
Objective. To evaluate the evolution of the COVID-19 pandemic in countries of the Americas, comparing health system data from before the appearance of the virus in the Region, accumulated cases and deaths before the deployment of public immunization strategies, and the current state of vaccination. Methods. An HJ-Biplot multivariate analysis and cluster analysis were performed for 28 countries in the Region of the Americas at three points in time: December 2019, December 2020, and December 2021. Results. In the Americas, heterogeneity was observed in the actions implemented to contain the pandemic, and this was reflected in different groups of countries. Conclusions. Not all countries in the Region of the Americas had the health conditions necessary to contain COVID-19. At the end of 2019, the United States, Canada, Brazil, and Cuba had advantages over other countries in the Region; however, actions implemented during 2020 to contain the pandemic created different groups of countries in terms of the prevalence of infections and deaths. At the end of 2020, Bolivia, Ecuador, and Mexico had critical levels of mortality. At the end of 2021, after the implementation of vaccination plans, more than 60% of the population of Argentina, Brazil, Canada, Chile, Colombia, Costa Rica, Cuba, Panama, the United States, and Uruguay had completed the vaccination schedule. © 2022 Pan American Health Organization. All rights reserved.